The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fcvm.2021.676694
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic Myocarditis: A Poorly Recognized Etiology of Left Ventricular Dysfunction in Valvular Heart Disease Patients

Abstract: Background: Heart failure occurs in ~10% of patients with acute rheumatic fever (RF), and several studies have shown that cardiac decompensation in RF results primarily from valvular disease and is not due to primary myocarditis. However, the literature on this topic is scarce, and a recent case series has shown that recurrent RF can cause ventricular dysfunction even in the absence of valvular heart disease.Methods: The present study evaluated the clinical, laboratory and imaging characteristics of 25 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Rheumatic heart disease, a systemic immune process provoked by a beta-hemolytic streptococcal infection, represents the most frequently acquired heart disease in developing countries [44]; despite it classically involving valves, and it has been reported that at least 10% of patients develop a secondary HF due to valve involvement, recent evidence showed that 25-30% of subjects undergoing heart transplantation had non-diagnosed myocarditis, leading to refractory heart failure and, ultimately, heart transplantation [45].…”
Section: Specific Forms Of Myocarditismentioning
confidence: 99%
See 1 more Smart Citation
“…Rheumatic heart disease, a systemic immune process provoked by a beta-hemolytic streptococcal infection, represents the most frequently acquired heart disease in developing countries [44]; despite it classically involving valves, and it has been reported that at least 10% of patients develop a secondary HF due to valve involvement, recent evidence showed that 25-30% of subjects undergoing heart transplantation had non-diagnosed myocarditis, leading to refractory heart failure and, ultimately, heart transplantation [45].…”
Section: Specific Forms Of Myocarditismentioning
confidence: 99%
“…Recently, it has been shown that about 70% of patients with rheumatic heart disease display a positive 18F-FDG PET/CT and that 90% of patients have a positive uptake of t-gallium-67 cardiac scintigraphy, regardless of LVEF [44].…”
Section: Imaging Biomarkersmentioning
confidence: 99%